1983
DOI: 10.2466/pms.1983.57.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Group Embedded Figures Test with Children

Abstract: Extensive previous research suggests that the cognitive style of field-independence/field-dependence has important implications for teaching and guidance. However, studies of the validity of group-administered measures which can be used with younger children are limited. The present study assessed the feasibility of using a widely recognized style measure, the Group Embedded Figures Test, with 45 fourth-, 42 fifth-, and 42 sixth-graders. The results were generally favorable with respect to the test's applicabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Disembedding ability was assessed by use of the Group Embedded Figures Test (Dumsha, Minard, & McWilliams, 1973;Thompson, Pitts, & Gipe, 1983;Witkin, Moore, Goodenough, & Cox, 1977;Witkin, Oltman, Raskin, & Karp, 1971). The test requires students to locate and outline simple figures concealed in complex and potentially misleading backgrounds.…”
Section: Instrumentsmentioning
confidence: 99%
“…Disembedding ability was assessed by use of the Group Embedded Figures Test (Dumsha, Minard, & McWilliams, 1973;Thompson, Pitts, & Gipe, 1983;Witkin, Moore, Goodenough, & Cox, 1977;Witkin, Oltman, Raskin, & Karp, 1971). The test requires students to locate and outline simple figures concealed in complex and potentially misleading backgrounds.…”
Section: Instrumentsmentioning
confidence: 99%
“…The results of Witkin and colleagues' research show that the test can be applied in a wide range of age groups. Thompson, Pitts and Gipe (1983) conducted research on the applicability of the Group Embedded Figure Test in the fourth, fifth and sixth grades. The results showed that the test was applicable in these age groups.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…The group administered Group Embedded Figures Test (Dumsha, Minard & McWilliams, 1973;Thompson, Pitts & Gipe, 1983;Witkin, Moore, Goodenough & Cox, 1977;Witkin, Oltman, Raskin & Karp, 1971) was used to assess disembedding ability. The test requires students to locate and outline simple figures concealed in complex and potentially misleading backgrounds.…”
Section: Instrumentsmentioning
confidence: 99%